Diagnostic and Prognostic Validity of Proadrenomedullin among Neonates with Sepsis in Tertiary Care Hospitals of Southern India - Raja Kannan; Suchetha S. Rao; Prasanna Mithra; B. Dhanashree; Shantharam Baliga; Kamalakshi G. Bhat (International Journal of Pediatrics)
Introduction. To evaluate Proadrenomedullin (Pro-ADM) as the diagnostic and prognostic marker in neonatal sepsis. Materials and Methods. In this cross-sectional study, Pro-ADM levels were estimated in 54 neonates with clinical sepsis and positive sepsis screen (cases) and 54 controls without clinical sepsis. Repeat Pro-ADM levels were estimated after 72 hours in cases. Pro-ADM levels were compared with the clinical outcome. Results and Discussion. Median Pro-ADM levels in cases were 31.8 (IQR: 27.8-39.4) pmol/ml which was significantly higher than controls 5.1 (IQR; 3.1-7.7) pmol/ml. From the constructed ROC curve, a value of 14.5 pmol/ml was taken as the cut-off for sepsis. Pro-ADM had 100% sensitivity, specificity, and positive predictive values (PPV) in detecting sepsis at 14.5 pmol/ml. Among cases, a decrease in Pro-ADM level by 10 pmol/ml was associated with 99% survival. Pro-ADM value of 35 pmol/ml had 100% specificity and PPV in predicting mortality. Conclusion. Pro-ADM can be used as a single biomarker for detecting neonatal sepsis, predicting clinical outcome and prognosis.